2021
DOI: 10.3390/ijerph18157726
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of a Percussive Massage Treatment on Movement Velocity during Resistance Training

Abstract: The aim of this research was to verify whether the application of percussion therapy during inter-set rest periods increases the number of repetitions performed before reaching a 30% velocity loss threshold during a bench press exercise. Methods: Twenty-four male university students participated in this study (24.3 ± 1.3 years; 77.5 ± 8.3 kg; 177.0 ± 5.6 cm; 24.7 ± 2.6 kg∙m−2). Participants were randomized into two groups: a percussion therapy group (PTG) and a control group (CG). They performed 4 sets at 70% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 36 publications
1
35
0
Order By: Relevance
“…Nevertheless, 5 min after PM, the Achilles tendon passive stiffness returned to the baseline value with a concomitant and insignificant decrease in drop jump height. Regarding the influence of mechanical PM on physical fitness, these results are partially consistent with the reports to date [ 7 , 9 ]. A study by Konrad et al [ 9 ] reveals no effect of 5 min mechanical PM on calf muscles on plantar flexor strength.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Nevertheless, 5 min after PM, the Achilles tendon passive stiffness returned to the baseline value with a concomitant and insignificant decrease in drop jump height. Regarding the influence of mechanical PM on physical fitness, these results are partially consistent with the reports to date [ 7 , 9 ]. A study by Konrad et al [ 9 ] reveals no effect of 5 min mechanical PM on calf muscles on plantar flexor strength.…”
Section: Discussionsupporting
confidence: 91%
“…A study by Konrad et al [ 9 ] reveals no effect of 5 min mechanical PM on calf muscles on plantar flexor strength. While Garcia-Sillero et al [ 7 ] even showed increased bench press repetitions when the mechanical PM was applied between sets. Moreover, McKechnie et al [ 23 ] showed that the manual tapotement massage, which is a similar technique to PM, of 3 min (of each calf muscle) did not affect the drop jump performed immediately after.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only three studies [ 64 , 66 , 69 ] provided sufficient information regarding the method of randomization and were therefore at a low risk of an order effect bias. The remaining studies were classified as an unclear risk as they did not provide sufficient information regarding the method of randomization.…”
Section: Resultsmentioning
confidence: 99%